Application of the Discovery Learning Model to Improve Understanding of Concepts and Learning Interests of Grade 3 Students Using Data Presentation Board Media - Ain, Nurul; Karomiah, Khandyas Kenza; Zuhro, Luluk Faridatus (Pelita : Jurnal Kajian Pendidikan dan Pembelajaran Indonesia, 2025)
This research aims to increase the interest in learning and understanding of mathematical concepts of grade III elementary school students in data presentation materials through the Discovery Learning model assisted by Data Presentation Board media with a teaching approach according to the level of students' ability. Based on initial observations at Bandungrejosari 1 Public Elementary School, Malang City, it is known that students have low interest in learning and have difficulty understanding the concept of data presentation. This classroom action research was carried out in two cycles over four meetings, involving observation, learning interest questionnaires, and learning outcome tests. Success indicators are set when ≥85% of students achieve a minimum score of 70. The results showed a significant increase, where the average value of concept comprehension increased from 68.3 in the pre-cycle to 83.3 in the second cycle, and the completeness of learning increased from 48% to 89%. The average learning interest score also increased from 71 to 86.3. These findings prove that the Discovery Learning model assisted by Data Presentation Board media is effective in increasing learning interest and understanding of mathematical concepts. Practically, these results recommend the use of a combination of discovery models and visual-based concrete media as an innovative alternative in mathematics learning in primary schools.